The SOX9-MMS22L Axis Promotes Oxaliplatin Resistance in Colorectal Cancer - Liu, Yiqiang; Wu, Hong; Luo, Tao; Luo, Qiyu; Meng, Ziyu; Shi, Ying; Li, Feifei; Liu, Mingxin; Peng, Xinhao; Liu, Junjie; Xu, Chuan; Tang, Weizhong (Frontiers in Molecular Biosciences, 2021)
Background: Colorectal cancer (CRC) estimated to be one of the most common cancer and the leading cause of cancer-related death worldwide. SOX9 is commonly overexpressed in CRC and participates in drug resistance. DNA damage repair confers resistance to anticancer drugs. However, the correlation of DNA damage repair and highly expressing SOX2 is still unclear. In this study, we aimed to investigate the function and the specific underlying mechanism of SOX9-dependent DNA damage repair pathway in CRC. Methods: The expression level of SOX9 and MMS22L in CRC were examined by immunohistochemistry and TCGA analysis. RNA sequencing was conducted in loss of SOX9 RKO cells and RKO shControl cells. The mechanistic studies were performed in CRC cell by modulating SOX9 and MMS22L expression. Drug sensitivity and DNA damage repair signaling events were tested. In addition, we investigated the effect of oxaliplatin in tumors with overexpressing SOX9 and low-expressing MMS22L in vivo. Results: Our study showed that SOX9 has a higher expression level compared to that in normal tissues, and predicts poor prognosis of CRC patients. Overexpression and knockdown of SOX9 were associated with the efficacy of oxaliplatin. In addition, SOX9 was enriched in DNA damage repair pathway by regulating MMS22L expression and participating in DNA double strand break. It upregulated and formed a complex with MMS22L, which blocked the nuclear translocation of MMS22L upon oxaliplatin treatment. What’s more, xenograft assay showed that oxaliplatin abrogated the tumor growth of MMS22L down-regulated cells in mice. Conclusions: In CRC, SOX9-MMS22L dependent DNA damage repair pathway is a core event regulating oxaliplatin sensitivity. Targeting this pathway is a promising therapeutic target in oxaliplatin-resistant CRC cells. Keywords: SOX9, MMS22L, DNA damage repair, oxaliplatin resistance.